2016
DOI: 10.1016/j.bbcan.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis: an alternative cell death program defending against cancer

Abstract: One of the hallmarks of cancer is resistance to programmed cell death, which maintains the survival of cells en route to oncogenic transformation and underlies therapeutic resistance. Recent studies demonstrate that programmed cell death is not confined to caspase-dependent apoptosis, but includes necroptosis, a form of necrotic death governed by Receptor-Interacting Protein 1 (RIP1), RIP3, and Mixed Lineage Kinase Domain-Like (MLKL). Necroptosis serves as a critical cell-killing mechanism in response to sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(125 citation statements)
references
References 124 publications
3
120
0
2
Order By: Relevance
“…S9). Our results are in accordance to the previous computer simulation study involving artificial membrane which suggested the translocation of large graphene sheets inside membrane via penetration compared to small sheets46. Including this, the presences of negatively charged groups on the surface of GO provide a strong electrostatic interaction between GO sheets and membrane leading to close interaction and provoke a physical damage which could be accounted for their presence in the cell cytoplasm4748.…”
Section: Resultssupporting
confidence: 92%
“…S9). Our results are in accordance to the previous computer simulation study involving artificial membrane which suggested the translocation of large graphene sheets inside membrane via penetration compared to small sheets46. Including this, the presences of negatively charged groups on the surface of GO provide a strong electrostatic interaction between GO sheets and membrane leading to close interaction and provoke a physical damage which could be accounted for their presence in the cell cytoplasm4748.…”
Section: Resultssupporting
confidence: 92%
“…Recently, a growing number of studies indicate necroptosis, distinct from apoptosis and necrosis, as a new mechanism of cell death (63). Cells can readily switch from one form of death to another (64).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this kind of switch is not known and is an interesting area of investigation for future studies. It is known though that regulated necrosis induced by multiple triggers involves receptor interacting protein kinase-1 (RIP-1) activating receptor interacting kinase-3 (RIP-3) and forming a complex of RIP1/RIP3 called necrosome complex 33 . Activated RIP3 then phosphorylates the downstream substrate that leads to membrane disruption.…”
Section: Discussionmentioning
confidence: 99%